Tetrahydrofuran alpha-azido esters: Precursors of anomeric alpha-amino acid monomers via radical bromination - Smith, M; Long, D; Martin, A; Campbell, N; Bleriot, Y; Fleet, G (1999)
A general route for the synthesis of tetrahydrofuran α-azido esters as the equivalent of monomeric furanose anomeric α-amino acids is described. Highly selective radical bromination of a range of suitably protected carbohydrate C-glycosyl derivatives affords bromo-esters which undergo efficient displacement by azide to give anomeric α-amino acid derivatives.